Facilitating Change in Drinking Cognitions and Behaviors Among Three Immigrant Generations of Latinx Youth Through a School-Based Intervention: Findings From a Multi-Site Clinical Trial - Bacio, Guadalupe A.; Garcia, Tracey A.; Anderson, Kristen G.; Brown, Sandra A.; Myers, Mark G. (Frontiers in Psychiatry, 2020)
Latinx youth experience disparities in the availability of and participation in evidence-based interventions to reduce hazardous alcohol use. The aim of this secondary data analysis was to examine whether Project Options, a brief, evidence-based alcohol use intervention was beneficial for Latinx participants. A total of 331 first-, second-, and third-generation immigrant Latina and Latino youth who participated in a multi-site, hybrid effectiveness/efficacy clinical trial of the intervention were selected for analyses. Mixed-effects growth models tested changes in drinking cognitions (i.e., perception of peer drinking, intention to drink next month, alcohol use and cessation expectancies) and behaviors (i.e., number of past-month drinking days, average number of drinks per occasion, and maximum number of drinks per occasion) across three time points (i.e., baseline, 4-weeks, and 12-weeks). Consistent with prior Project Options studies, participants with more drinking experience reported greater decreases in perception of peer drinking, intentions to drink next month, and all drinking behaviors than those with less experience. While no changes were observed in expectancies, first-generation participants endorsed lower positive use expectancies than second- and third-generation youth as well as more favorable cessation expectancies than third-generation teens. In concert with prior studies demonstrating the intervention’s success in recruitment and retention of Latinx participants, results suggest that Project Options might be a promising school-based intervention for Latinx youth. This intervention has the potential to reach adolescents who might otherwise not participate in traditional programming and help decrease disparities in availability of evidence-based practices for Latinx youth.